Analisis Penerimaan Aplikasi Naskah Dinas Elektronik (Nadine) Di Biro Umum Sekretariat Jenderal Kementerian Keuangan Menggunakan Technology Acceptance Model (TAM) - Juliansyah, Eddy; Lawanda, Ike Iswari (Khazanah: Jurnal Pengembangan Kearsipan, 2024)
One of the impacts of the rapid development of information and technology (IT) in the archives sector is the presence of an electronic records management system (ERMS). Many ERMS has been developed, but not all of them have been successfully implemented. One important factor in its implementation is user acceptance. User acceptance influences user intentions when using an ERMS application. One of the ERMS is the Naskah Dinas Elektronik (Nadine) application atthe Ministry of Finance, which was implemented five years ago but has not yet been tested for user acceptance. This research was conducted to analyze the factors involved in accepting Nadine's application at the General Bureau as Centre Archives of the Ministry of Finance through the technology acceptance model (TAM). The research method used was quantitativedescriptive, with questionnaires distributed to 72 respondents using the Nadine application at the General Bureau. The data obtained was processed using a non-parametric statistical method, namelypartial least squares structural equation modelling (PLS-SEM). The research results show that system quality factors, user training factors, and facility conditions significantly influence user intentions when using the Nadine application. Perceived ease of use and perceived usefulness show a positive correlation with intention to use. Perceived usefulness has a significant direct influence on intention to use, while perceived ease of use has an indirect influence on intention to use through perceived usefulness. The implications of this research provide suggestions for policymakers to improve the quality of implementation of the Nadine application by improving system quality, providing training programs, and providing adequate facilities. This research can also be used to explore factors that influence users' intentions to accept ERMS, especially perceived usefulness and perceived ease of use.